Comprehensive Evaluation of Agricultural Residues Corn Stover Silage - Pilong Zhou; Guofang Wu; Xuan Luo; Yuhong Ma; Kaiwen Guan; Huili Pang; Zhongfang Tan; Shiyan Zhang; Lei Wang (Agriculture, 2025)
As a typical agricultural waste, the resource utilization of corn stover (CS) plays a crucial role in the coordinated optimization of ecological and economic benefits. In order to enhance the utilization of CS resources, Lentilactobacillus (L.) buchneri (LB) and different proportions of Artemisia argyi (AA) were added to CS to investigate the impact of additives on the fermentation quality and aerobic stability of corn stover silage (CSS). This study revealed that the separate addition of AA or LB in CS effectively improved the silage quality and aerobic stability. Specifically, LB exhibited the lowest pH value of 3.72 at 90 d of fermentation, while the NH3-N content was 0.07 g/kg DM during the anaerobic fermentation stage and 0.19 g/kg DM during the aerobic exposure stage (p < 0.05). Mixing 30% AA increased the lactic acid content, lowered the pH, maintained a higher relative abundance of Lactobacillus, and reduced mycotoxin levels. In terms of aerobic stability, all AA-treated groups demonstrated superior performance compared to the LB treatment. Additionally, it was observed, that in the 30% AA group, Candida exhibited the highest relative abundance. Importantly, the addition of AA upregulated carbohydrate metabolism and lipid metabolism during the ensiling process, and their relative abundances remained high during aerobic exposure. Fully utilizing CS resources as feed to provide fiber and nutrients for ruminants can not only reduce the pressure on forage demand but meet the development needs of “grain-saving” animal husbandry, which is conducive to solving the contradictions of “human–animal competition for food” and “human animal competition for land”.